Ozone protects cardiomyocytes against ischemia/reperfusion injury: Regulating the heat shock protein 70 (HPS70) expression through activating the JAK2/STAT3 Pathway. Issue 1 (1st January 2021) - Yu, Shenglong; Guo, Huizhuang; Luo, Yi; Chen, Hanwei
ABSTRACT: Ischemia/reperfusion (I/R) injury causes complications in early coronary artery reperfusion for acute myocardial infarction (AMI). Ozone (O3 ) has been reported to be applied for protecting I/R injury, but its detailed mechanism remains unclear. Our study focused on the protective effect of O3 pretreatment on myocardial I/R injury and JAK2/STAT3 signaling and HSP70 regulation involving in the mediation. The rat hearts which were perfused and isolated as well as the cultured cardiomyocytes of neonatal rat were exposed to hypoxia/reoxygenation (H/R) and different concentrations of O3 followed by heat shock protein 70 (HSP70) siRNA treatment. The results showed O3 attenuated the suppression of cell viability induced by H/R and decreased the release of activity of creatine kinase (CK), lactate dehydrogenase (LDH) and apoptosis of cardiomyocytes in vitro . Moreover, O3 also activated the JAK2/STAT3 signaling, upregulated the expression of HSP70 both in vitro and vivo, and decreased the index of apoptosis of cardiomyocytes caused by I/R as well as myocardial infarct area in vivo . In addition, HSP70 siRNA and JAK2 inhibitor AG490 inhibited the cardioprotective effect of O3 . And the expression of HSP70 increased by ozone was reduced by AG-490. In conclusion, our results demonstrated that ozone protects cardiomyocytes in I/R injury through regulation of the expression of HSP70 by activating the JAK2/STAT3 pathway.